A espeleologia e as cavernas no Ceará: conhecimentos, proteção ambiental e panorama atual - Monteiro, Felipe Antônio Dantas (2014)
In Ceará, plus the famous Grotto of Ubajara, there are many other caves in this way, it is essential to know the current situation to achieve this speleologically protect it. Speleology, which is the study of caves has revealed to mankind the great importance of these environments. In addition to having served as a shelter for man in prehistoric times, the caves are as natural and cultural storehouses of valuable scientific records, paleontological, archaeological, among others. The cave environments also stand out due to its beautiful scenery of rock formations, ornamented by speleothems (stalactites, stalagmites, etc.) and their subterranean ecosystems, peculiar and fragile, with endemic and rare species, like the troglodyte. Natural underground cavities, popularly known like caves, grottos, caves, burrows, limpets, pits or holes, are considered by the Federal Constitution as "property of the Union" in the country and there is a specific, relevant to the protection of the Brazilian speleologically legislation. Cavers in Brazil estimated that only about 5% of the existing caverns have been identified. In Ceará, many of the known caves are not officially registered in the National Speleological entries. For this reason, this dissertation aims to present the current landscape of speleologically in Ceará. For this are worked in research knowledge and concepts related to caving, as its importance, use, weaknesses and impacts; relevant legislation for the protection, licensing and environmental conservation speleologically; and the current survey information on the known caves in the territory of Ceará, with recommendations for their use and conservation. It is intended this way, based on this overview, base public policies on environmental protection and management of natural underground cavities and areas of potential occurrence.